Sero epidemiological study on human T Lymphotrophic Virus type 1 among patients with haematological and other malignancies in Cancer Institute, Maharagama - Kothalawala, M (My University, 2005)
Carcinoma of the stomach, Carcinoma of the Oesophagus, Biabetic Foot, Carcinoma of the Rectum, Early Breast Cancer, Perforated Duodenal Ulcer-an unusual presentation, Acute Calculous Cholecystitis, Acute Extradural Haemorrhage, Gracture of the Shaft of Femur, Non Functioning Kidney.